THE INFLUENCE OF SERVICE QUALITY AND SATISFACTION ON CUSTOMER LOYALTY MNC VISION KPP BOGOR - Ela Hulasoh (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The problem in this research is how much influence service quality has on MNC Vision KPP Bogor customers, to find out how much influence satisfaction has on MNC Vision KPP Bogor customer loyalty, and to find out how much influence service quality and satisfaction have on MNC Vision KPP Bogor customer loyalty. So the purpose of this study is to find out how much influence service quality has on customer loyalty MNC Vision KPP Bogor, to find out how much influence customer satisfaction has on customer loyalty MNC Vision KPP Bogor, and to find out how much influence service quality and customer satisfaction have on customer loyalty. MNC Vision KPP Bogor. The method used is quantitative associative, which aims to determine the relationship between two or more variables. This study links service quality and customer satisfaction as independent variables and customer loyalty as the determined variable. The large population in this research object used the Rao Purba sampling technique of 96 respondents (customers), with accidental sampling technique. The results showed that the coefficient of determination (R Square) obtained was 0.551. This means that 49.9% of customer loyalty is influenced by variables of service quality and customer satisfaction, while 55.1% is influenced by other variables not examined in the study such as promotion, price, product, location and image. Thus it is said that H0 is rejected and Ha is accepted, which means that there is a simultaneous influence between service quality and customer satisfaction with customers together.